2005
DOI: 10.1016/j.jvs.2004.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Femoral vein transposition for arteriovenous hemodialysis access: Improved patient selection and intraoperative measures reduce postoperative ischemia

Abstract: Improved patient selection and selective intraoperative femoral vein tapering eliminated remedial procedures to correct ischemia in patients undergoing tFV access. Patency rates were excellent despite the liberal use of vein tapering. Transposed FV access should be considered for good risk individuals undergoing their first lower extremity access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 18 publications
0
70
0
1
Order By: Relevance
“…Gradman et al (14,15) reported a low thrombosis rate in 25 patients with transposed superficial femoral vein (tFV) AVF with mean follow-up of 9.1 months. The cumulative primary and secondary fistula patency rates were 78% and 73% at 6 and 12 months and 91% and 86% at 6 and 12 months, respectively.…”
Section: Transposed Femoral Vein Le-avfmentioning
confidence: 99%
See 1 more Smart Citation
“…Gradman et al (14,15) reported a low thrombosis rate in 25 patients with transposed superficial femoral vein (tFV) AVF with mean follow-up of 9.1 months. The cumulative primary and secondary fistula patency rates were 78% and 73% at 6 and 12 months and 91% and 86% at 6 and 12 months, respectively.…”
Section: Transposed Femoral Vein Le-avfmentioning
confidence: 99%
“…The cumulative primary and secondary fistula patency rates were 78% and 73% at 6 and 12 months and 91% and 86% at 6 and 12 months, respectively. One patient needed above knee amputation for acute compartment syndrome, and eight patients required a second surgery for distal limb ischemia (14,15). Rueda et al (16) reported 10 patients with tFV LE-AVF accesses, and none had a lower extremity ischemic event.…”
Section: Transposed Femoral Vein Le-avfmentioning
confidence: 99%
“…However, if the upper limb use is not appropriate, axillary-axillary AV access (necklace graft) (25), superficial femoral vein transposition (26), axillary artery to right atrial graft (27), hemodialysis reliable outflow graft (28), and femoral AV graft could be used as alternative choices for vascular access (19)(20)(21). Autogenous AV fistula or graft AV fistula are available for femoral AV access, although the former is not preferred because of wide incision and associated complications (19,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Despite of having reported low incidence of CVI, steal syndrome is a major concern as well. Grandman and collaborators 5,16 reported 8 cases of steal syndrome in a series of 25 patients, including a case of amputation due to compartmental syndrome.…”
Section: Discussionmentioning
confidence: 99%